Bibliometric Analysis of Smart Cities and Tourism Studies with Visual Mapping Technique - Yapici, Olcay Ozisik (Univ Caxias Sul, Programa Pos-graduacao & Turismo, 2022)
Smart cities, where technological innovations are used and which provide easy access to information in the city where both local people and tourists are located, may have the potential to become prominent cities in terms of tourism. In the study, the bibliometric method with the Vosviewer package program was used. 1050 studies obtained from the Web of Science data platform were examined, which contain smart city and tourism. The obtained data were analyzed using the visual mapping technique. According to the collocation analysis made on the keywords, twelve different themes were determined and grouped as smart city, tourism, smart tourism destination, tourism. Within the scope of the research, most of the studies are congress papers. In the literature, it has been determined that the subject of the smart city is mainly associated with the concepts of destination, internet, sustainability, accessibility, big data, tourism. According to the findings, the studies started in 2000 and increased in 2020. Engineering, computers and tourism are the disciplines where most studies are done.
Keywords: Tourism; Smart City; Bibliometric; Visual Mapping